Conventional and molecular diagnostic strategies for prosthetic joint infections. (January 2014) - Esteban, Jaime; Sorlí, Luisa; Alentorn-Geli, Eduard; Puig, Lluís; Horcajada, Juan P
Abstract : An accurate diagnosis of prosthetic joint infection (PJI) is the mainstay for an optimized clinical management. This review analyzes different diagnostic strategies of PJI, with special emphasis on molecular diagnostic tools and their current and future applications. Until now, the culture of periprosthetic tissues has been considered the gold standard for the diagnosis of PJI. However, sonication of the implant increases the sensitivity of those cultures and is being increasingly adopted by many centers. Molecular diagnostic methods compared with intraoperative tissue culture, especially if combined with sonication, have a higher sensitivity, a faster turnaround time and are not influenced by previous antimicrobial therapy. However, they still lack a system for detection of antimicrobial susceptibility, which is crucial for an optimized and less toxic therapy of PJI. More studies are needed to assess the clinical value of these methods and their cost–effectiveness.